-(-4v-y)-4(-5y+6v)=

Simple and best practice solution for -(-4v-y)-4(-5y+6v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-4v-y)-4(-5y+6v)= equation:


Simplifying
-1(-4v + -1y) + -4(-5y + 6v) = 0
(-4v * -1 + -1y * -1) + -4(-5y + 6v) = 0
(4v + 1y) + -4(-5y + 6v) = 0

Reorder the terms:
4v + 1y + -4(6v + -5y) = 0
4v + 1y + (6v * -4 + -5y * -4) = 0
4v + 1y + (-24v + 20y) = 0

Reorder the terms:
4v + -24v + 1y + 20y = 0

Combine like terms: 4v + -24v = -20v
-20v + 1y + 20y = 0

Combine like terms: 1y + 20y = 21y
-20v + 21y = 0

Solving
-20v + 21y = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-21y' to each side of the equation.
-20v + 21y + -21y = 0 + -21y

Combine like terms: 21y + -21y = 0
-20v + 0 = 0 + -21y
-20v = 0 + -21y
Remove the zero:
-20v = -21y

Divide each side by '-20'.
v = 1.05y

Simplifying
v = 1.05y

See similar equations:

| x^4+8x^3+32x^2+64x+64=0 | | 6x^7-6xy^10=0 | | s^3+12s^2-4s-48=0 | | 1490000=8x+7(20000-x) | | -y^2-9y^2= | | -5/7x-6-7 | | 4n-20=7(-2n+2) | | ln(6x+3)=ln(4x+1) | | 330000=24000-x | | (x-y*lny+y*lnx)*dx+x*(lny-lnx)*dy=0 | | (w-11)(w^2-11w+28)=0 | | 5x+26=4x+7 | | (m^1/3n^7/3)^3/4 | | 330000=3x+24000-2x | | (y+6)(y+1)=-6 | | 9x^4+72x^3+48x^2+576x+576=0 | | 2x^3(-4x^3+8x-3)= | | 56x-4=52 | | 6x^(2/3)-5x^(1/3)-1=0 | | 4d=5+3d | | 4z(2z-3)=2z-3 | | 30x^2-464x-2500=0 | | 5/6(T)=2/3 | | 2(4s+5)-4s=2(2s+1)-5 | | 38735=x+x(.27) | | 38735=x-x(.27) | | 10-(3z-4)=3-4z | | 6n-7=28.4 | | 484.50=x-x(.05) | | 23.20=x-x(0.20) | | -21-28+x=-37 | | 9x-7=44-8x |

Equations solver categories